Implications of COVID-19 for conflict in Africa - Charlotte Fiedler; Karina Mross; Yonas Adaye Adeto (Deutsches Institut für Entwicklungspolitik (DIE), 2021)
How has the COVID-19 pandemic affected armed conflict and political violence within countries? Focusing on Africa, a continent with a particularly high number of ongoing conflicts, this policy brief analyses the immediate and long-term implications of the pandemic on conflict and reflects on its implications for international peacebuilding efforts. In the short term, conflict patterns on the continent are marked more by a continuation of previous trends than by a strong direct impact of COVID-19. Regarding armed confrontations, there was a rise in conflict intensity in some countries and one new war erupted in the Tigray region of Ethiopia in November 2020. As to lower-scale political violence, especially in the beginning of the pandemic, many states used excessive state violence against civilians when enforcing Corona measures. Perhaps more important than the immediate effect of the pandemic, the consequences of the pandemic are very likely to accelerate violent conflict in the medium to long term. This is firstly because the pandemic exacerbates structural weaknesses, including the sharpening of societal divisions, severe disruptions in the education sector and deteriorating socio-economic circumstances. Secondly, the pandemic has curtailed actors and institutions that might be able to reduce the risk of violent escalation. Trust in the state and security institutions has suffered in many countries due to dissatis-faction with the handling of the pandemic. Moreover, democratic processes are hampered by the postponement of elections and increasing levels of government repression. At the same time, international peace support is negatively affected by social distancing and further threatened by looming cuts of commitments in official development assistance. Bringing together both the short-term and longer-term effects of the pandemic on conflict clearly shows the risk that the pandemic poses to peace in Africa. It is therefore vital for the international community to: 1. Stay engaged and stay alert. If the international community continues to focus on handling the domestic consequences of the pandemic rather than international challenges, conflict will further increase in intensity and spread geographically. COVID-19 has already led to a reduction in international peace support, including peacebuilding initiatives and mediation. However, these instruments are vital to foster peace and prevent emerging and renewed conflict. 2. Invest in conflict prevention. The adverse effects of COVID-19 on economic, social and political structures can, and very likely will, provide the breeding ground for larger-scale conflicts, both in least developed countries (LDCs) and middle-income countries. Thus, conflict prevention must be taken seriously, including the strengthening of open and participatory (democratic) processes that enable societies to deal with societal conflicts peacefully. 3. Pay special attention to post-conflict countries. Many African countries have experienced large-scale civil wars in their history and continue to be LDCs struggling with societal tensions. The risk of renewed conflict in these places is particularly high.
Keywords: 330